C-terminal troponin-I residues trap tropomyosin in the muscle thin filament blocked-state - Lehman, William (Biochem Biophys Res Commun, 2021)
Tropomyosin and troponin regulate muscle contraction by participating in a macromolecular scale steric-mechanism to control myosin-crossbridge – actin interactions and consequently contraction. At low-Ca(2+), the C-terminal 30% of troponin subunit-I (TnI) is proposed to trap tropomyosin in a position on thin filaments that sterically interferes with myosin-binding, thus causing muscle relaxation. In contrast, at high-Ca(2+), inhibition is released after the C-terminal domains dissociate from F-actin-tropomyosin as its component switch-peptide domain binds to the N-lobe of troponin-C (TnC). Recent, paradigm-shifting, cryo-EM reconstructions by the Namba group have revealed density attributed to TnI along cardiac muscle thin filaments at both low- and high-Ca(2+) concentration. Modeling the reconstructions showed expected high-Ca(2+) hydrophobic interactions of the TnI switch-peptide and TnC. However, under low-Ca(2+) conditions, sparse interactions of TnI and tropomyosin, and in particular juxtaposition of non-polar switch-peptide residues and charged tropomyosin amino acids in the published model seem difficult to reconcile with an expected steric-blocking conformation. This anomaly is likely due to inaccurate fitting of tropomyosin into the cryo-EM volume. In the current study, the low-Ca(2+) cryo-EM volume was fitted with a more accurate tropomyosin model and representation of cardiac TnI. Our results show that at low-Ca(2+) a cluster of hydrophobic residues at the TnI switch-peptide and adjacent H(4) helix (Ala149, Ala151, Met 154, Leu159, Gly160, Ala161, Ala163, Leu167, Leu169, Ala171, Leu173) draw-in tropomyosin surface residues (Ile143, Ile146, Ala151, Ile154), presumably attracting the entire tropomyosin cable to its myosin-blocking position on actin. The modeling confirms that neighboring TnI “inhibitory domain” residues (Arg145, Arg148) bind to thin filaments at actin residue Asp25, as previously suggested. ClusPro docking of TnI residues 137–184 to actin-tropomyosin, including the TnI inhibitory-domain, switch-peptide and Helix H(4), verified the modeled configuration. Our residue-to-residue contact-mapping of the TnI-tropomyosin association lends itself to experimental validation and functional localization of disease-bearing mutations.